Mineralization and metallogenic model of the Laurani high-sulfidation epithermal deposit in northeastern Bolivian Altiplano - Fei Liu; Runsheng Han; Shuming Wen; Dong Zhao; Wenyao Li; Li Lei; Chaojian Qin; Yuxinyue Guo (Scientific Reports)
Abstract The Laurani high-sulfidation epithermal deposit, located in the northeastern Altiplano of Bolivia, is a representative gold-polymetallic deposit linked to the late Miocene volcanic rocks that were formed approximately at about 7.5 Ma. At Laurani, four mineralization stages are defined. Stage I primarily consists of ore-barren vuggy quartz that free with metal sulfides. Stage II and stage III generate four predominant styles of mineralization of explosive breccia-style Au–Cu, contact-style Cu–Au–Ag, hydrothermal vein-style Au–Ag–Cu–Pb–Zn and porphyry-style Au–Cu that with a diversity of occurrences, reflecting the strong lithological and structural controls. Stage IV is formed by supergene oxidation of earlier metalliferous minerals postdated the main mineralization. Hydrothermal alteration is characterized by significant intensity and zoning, with phyllic alteration at the center, surrounded by propylitic alteration, and further overlapped by extensive argillic alteration. Additionally, the well-developed quartz–alunite–barite tends to be found along or in close proximity to the hydrothermal vein-style orebodies. Fluid inclusions hosted in the stage I ore-barren quartz indicate that the ore-forming fluids predating predominant metal deposition are low- to moderate-salinity (0.2–23.1 wt.% NaCleq), high-temperature (90% of homogenization temperature > 300 ℃) and CO2-bearing fluids. Subsequently, through processes of boiling (~ 250 to 360 ℃), cooling and mixing with meteoric water, these fluids transform to low-salinity (4.2–6.9 wt.% NaCleq) and low-temperature (90% of homogenization temperature < 220 ℃) fluids. H–O isotopic compositions obtained from the stage I ore-barren quartz and the stage II quartz vein and barite vein have δD =  − 101.50 to − 41.31‰ and δ 18OH2O = 5.66 to 12.27‰, demonstrating a trend extending from magmatic composition to meteoric water, which suggest that the ore-forming fluids are mostly magmatic water, mixing with a little meteoric water. δ 34S values of sulfides from the stage II and stage III are 1.57–5.55‰, while barites from the stage II in textural equilibrium with sulfides own δ 34S values of 24.01–25.90‰, reflecting a magmatic origin and H2S is the dominant species of sulfur. Pb isotope signatures of Laurani ores (206Pb/204Pb = 18.2869–18.3568, 207Pb/204Pb = 15.6082–15.6337 and 208Pb/204Pb = 38.6937–38.7719) are consistent with those of the Arequipa Massif basement located beneath the Altiplano, indicating that Pb originates initially from the old, thickened lower crust of the Arequipa Massif. The study on mineralization at Laurani, along with the similar epithermal deposits that formed in the late Miocene in the Central Andes, suggests that the thickened lower crust could play a crucial role as a metal source for forming porphyry–epithermal deposits. Currently, the hydrothermal vein-style Au–Ag–Cu–Pb–Zn is the most important and economic mineralization that developed in the shallow part at Laurani. Moreover, the first discovery of porphyry-style Au–Cu within dacitic porphyry suggests a significant potential for the formation of a porphyry deposit at greater depths in the Laurani mine.